The effect of Garlium GEM HC as a tick repellent agent in springbok(Antidorcas marsupialis) - Koeppel, Katja Natalie (University of Pretoria, 2022)
Dissertation (MMedVet(Fer) (Wildlife))--University of Pretoria, 2020.